Semester students’ perceptions about online class during COVID-19 pandemic (Scholars' Journal, 2020)
Face-to-face delivery of education system had been greatly affected due to the outbreak of COVID-19. As an alternative to it, classes were run online wherever there was access to the Internet with technological devices. With this scenario, this study explored the perceptions of semester students about online class at master’s level during COVID-19 pandemic. By using the phenomenological research design of qualitative study, purposive sampling technique was used to collect the views of three students of master’s level studying at third and fourth semesters at an affiliated campus of Tribhuvan University (TU) and a constituent campus under Far Western University (FWU) of Nepal. Semi-structured online interview was conducted to collect the data. The result showed that the students were positive towards online delivery mode due to the need for getting education during COVID-19 pandemic.